Synthetic studies toward macrocidins: an RCM approach for the construction of the central cyclic core - Ramana, C. V.; Mondal, Mohabul A.; Puranik, Vedavati G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
The central macrocyclic core of the macrocidins was constructed using RCM as the key reaction. A preliminary investigation dealing with the key reactions, that is, the Dieckmann cyclization and the RCM, revealed that RCM of the beta-ketoamide is better than RCM of the corresponding acyltetramic acid. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: acyltetramic acid; Lacey-Dieckmann cyclization; macrocidins; Ring closing metathesis

Carbohydrate based approach towards the synthesis of aspercyclide C - Ramana, C. V.; Mondal, Mohabul A.; Puranik, Vedavati G.; Gurjar, Mukund K. (Tetrahedron Letter, 2007)
A formal total synthesis of aspercyclide C (3) is described in which D-ribose is employed as a chiral pool material. The key step is a ring closing metathesis. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: chiron approach; D-ribose; Mukaiyama reagent; ring closing metathesis (RCM); Ullmann coupling

Effect of the allylic substituents on ring closing metathesis: the total synthesis of stagonolide B and 4-epi-stagonolide B - Giri, Awadut G.; Mondal, Mohabul A.; Puranik, Vedavati G.; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2010)
The total syntheses of stagonolide B and its 4-epimer were carried out to probe into how the relative stereochemistry of allylic hydroxy groups and their protecting groups influence the efficiency of the ring closing metathesis.